Filling the Vacant Space: A Close Reading of Kant’s Dialectic of Pure Practical Reason - Saafan, Mae Ashraf Ali (AUC Knowledge Fountain, 2023)
The main aim of this thesis is to explore Kant’s central notion of rational belief. Kant’s account of rational belief could be viewed as the ground on which rational moral agents assent to propositions that enable them to avoid any practical incoherence as they engage in their moral duty. The paper will offer a close reading of the dialectic of pure practical reason, particularly the doctrine of the postulates of practical reason. In this doctrine, Kant argues that although there is no theoretical proof for or against freedom, God, and the immortality of the soul, rational moral agents ought to believe in their reality, as there are practical grounds to believe in them. The need to introduce these practical postulates is the necessity of a hypothesis that can and must be formed by the subject only from a practical point of view. This paper will show that not only could the postulates be viewed as a point of connection between what Kant conceives of as the phenomenal world of spatio-temporal appearances and the noumenal realm of things in themselves, but also as architectonic elements which – in their connection to the concept of freedom – are part of what “constitutes the keystone of the whole structure of a system of pure reason” (KpV, 5:3 f.) and thus also crucial for the conceivability of the unity of the theoretical and practical use of reason in accomplishing the “highest vocation of reason” (5:108), i.e., the actualization of the highest good.